Strategic management and value creation in non-profit organisations - Santos, Tânia (2021)
The present study aims to assess the impact of strategic management on value creation in Non-Profit Institutions (NPOs). The research is based on an online questionnaire applied to 67 directors of NPOs in the district of Leiria, located in the central region of Portugal, whose functions are focused on the definition and implementation of the strategic management of these institutions to fulfil their missions. This quantitative study found that the formulation and implementation of strategies directly positively impact value creation and that the formulation of strategies has an indirect positive impact, when mediated by the implementation of strategic choices, on the value creation of these same organisations. This study reinforces the theoretical argument that points to the growing importance of strategic management in this type of organisation's performance and value creation. It can also serve as a benchmark for leaders and managers to fulfil these organisations' missions. Finally, it was possible to identify a set of indicators that, in each dimension of the strategic management studied, can help create the most value.